Standard scores and levels for certain legal situations among first-class basketball referees - adnan, hasnain; Shabba , Faris; Mohammed , Khaleel (Journal of Physical Education, 2025)
The significance of the research lies in the fact that electronic technologies represent an important step in evaluating legal situations, and the research problem centered on the lack of attention to visual requirements and the absence of a clear image of legal situations that may be difficult for the referee to apply correctly in addition to the lack of focus on visual requirements and the unclear depiction of some legal cases which make it difficult for the referee to interpret them correctly This is because the referee's main tool is visual perception, which interprets live situations such as violations, fouls, and other cases that arise during a game Moreover, there are numerous responses and challenges in evaluating legal situations as the evaluation often relies on subjective or visual estimates based on the opinions of others, leading to inaccuracies in assessing refereeing performance.The objectives of the research were to prepare a set of legal situations for first-class basketball referees in Iraq, to design an electronic test for certain legal situations in basketball, and to identify the scores and standard levels for some legal situations in basketball The researchers used the descriptive survey method, and the research population consisted of 65 first-class basketball referees in Iraq To statistically analyze the data resulting from the test, the Statistical Package for the Social Sciences (SPSS) was used.In light of the results, several conclusions were reached, including the design and validation of the electronic test for some legal situations for first-class basketball referees in Iraq, which is the first of its kind in the Iraqi environment, setting reference standards to serve as criteria for evaluation, comparison, or selection, and determining the standard levels for the results of the electronic test for certain legal situations for first-class basketball referees in Iraq.